Teglproduktion i Danmark: Teglværkerne ved Bregnet og Auning samt en teglbrænders keramik - Kock, Jan; Guntzelnick Poulsen, Thomas; Harritz Rahbek, Nanna; Hansen, Helge (Kuml, 2025)
Brick and tile production in Denmark The brickworks at Bregnet and Auning and a brickmaker’s pottery The first traces of brick and tile production in Denmark date to the mid-12th century, when the vertical kiln appears to have been introduced to the country in a fully developed form. Brick- and tile-making became established across most of the country during the second half of the 12th century, almost as a wave, and not only on royal initiative, as was previously theorized (figs. 1-11). This brick kiln was then used in almost unaltered form until about 1900 and even into the 20th century. There are now more than 400 archaeological records of brick- and tile kilns from Denmark. Most are of the same construction, in the form of a vertical kiln where the stoking and kiln chambers are not separate. The two-part brick kiln only occurs in the Early Middle Ages. The focus here is on this type of kiln and its use through the centuries, as well as its origin and distribution. The archaeological record is supplemented here by a variety of records and eye-witness accounts. Attention is also focused on the overlooked phenomenon of clamp firing, i.e. the firing of bricks and tiles without constructing a kiln for the purpose (figs. 12-16). Against this background, two recently discovered brick-kiln sites are presented. One of these lies at Bregnet (figs. 17-29a-f) near Kalø castle, northeast of Aarhus, and functioned during the Middle Ages and Renaissance. Unusually many structures were preserved here, which demonstrate the production process from raw clay to finished product. The second kiln site was discovered at Auning (figs. 30-41), central Djursland, and is dated to the early 17th century. Two kilns were preserved here, one of which had been rebuilt several times. So much was preserved of the other kiln, it could be demonstrated that the kiln chamber had been vaulted and therefore furnished with a closed kiln chamber. This is the earliest example of its kind in Denmark. These brickworks supplied bricks and tiles for the nearby manor of Gammel Estrup and its church. The brickmaker’s dwelling lay close by and a large quantity of pottery from his household was preserved, including a remarkably large proportion of imported wares (figs. 42-44).